How Behavioral Aspects Affect Market Efficiency- Evidence from KSE 100 index (Global Journal of Management and Business Research, 2012)
Study of behavioral finance has been the focus of many researchers. Various researches as well as empirical analyses have been conducted in different stock markets of the world in order to verify the seasonal anomalies and to observe behavioral patterns of investors by which they earn abnormal returns. This research attempted to find anomalous behavior in two different sets of data. The first data set includes period of thirteen years from 1997 to 2010 and the second set of data consists of 11 years excluding the years of market crash 2005